Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen - Fitria, Astri; Yulianto, Anton Eko (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This research aimed to examine the effect of collateralizable assets, liquidity, profitability, and company growth on the dividend policy. This research was the quantitative method. Furthermore, the research population used LQ 45 companies listed on Indonesia Stock Exchange (IDX) during the 2016-2020 period. by purposive sampling method, it obtained 17 LQ 45 companies with 85 observations. Moreover, the research analysis technique used multiple linear regressions analysis. This research used the purposive sampling method, a sample selection with determining criteria. This research concluded that: (1) Collateralizable Assets did not affect the dividend policy, (2) Liquidity had a positive effect on the dividend policy, (3) Profitability showed a positive effect on the dividend policy. (4) Company’s Growth did not affect the dividend policy.